Advancing Breast Cancer Therapy with Iron Oxide Nanoparticles - Soumitra Mandal, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Breast cancer remains a leading cause of morbidity and mortality among women worldwide, presenting a pressing challenge for global health. The integration of nanotechnology into cancer care offers transformative opportunities to improve diagnostics, therapeutic interventions, and monitoring. Among various nanomaterials, iron oxide nanoparticles (IONPs) stand out for their distinctive physicochemical properties, including superparamagnetism, excellent biocompatibility, and the flexibility for surface functionalization. This article delves into the diverse applications of IONPs in breast cancer care, focusing on breakthroughs in imaging modalities, precision-targeted drug delivery systems, and innovative therapeutic strategies. By analyzing the latest research findings and clinical trial data, we present a detailed exploration of how IONPs can significantly advance the landscape of breast cancer management, paving the way for personalized and effective patient care.
Keywords: Iron Oxide Nanoparticles (IONPs); Nanomedicine; Cancer Theranostics; Breast Cancer Care; Targeted Drug Delivery